PEMILIHAN KEPALA NEGARA DI INDONESIA - Paisal Paisal (SOL JUSTICIA, 2018)
In the development of law in Indonesia, especially concerning the development of the application of Islamic law, Islamic law experienced ups and downs following the political direction that existed at that time, especially in the context of the election of head of state in Indonesia. It is interesting to raise the theme of the election of the head of state, given the actual dualism of opinions relating to this matter. Is the election of head of state directly from the people or the election of head of state through people's representatives. What really is the desire and purpose of the holders of power in the Unitary State of the Republic of Indonesia. From this phenomenon, the author is very interested in researching further with the focus: "Election of State Heads in Indonesia" This research will answer the problem statement, namely; what is the system of electing heads of state in Indonesia; In an effort to answer the problem in this study, the authors used research with a historical documentary approach. Then analyzed using content analysis. The results of the study indicate that the mechanism for the selection or appointment of heads of state in Indonesia theoretically and empirically has occurred with two models. First, through the highest state institution, the People's Consultative Assembly. Second, through direct elections from people who already have the right to vote.